The Role of Systemic Arterial Stiffness in Open-Angle Glaucoma with Diabetes Mellitus. (18th October 2015) - Shim, Seong Hee; Kim, Chan Yun; Kim, Joon Mo; Kim, Da Yeong; Kim, Yang Jae; Bae, Jeong Hun; Sung, Ki Chul
Abstract : Purpose. To investigate the role of systemic arterial stiffness in glaucoma patients with diabetes mellitus (DM). Design. Retrospective, cross-sectional study. Participants. DM subjects who underwent brachial-ankle pulse wave velocity (baPWV) were recruited. Methods. Glaucoma patients (n = 75 ) and age-matched control subjects (n = 92 ) were enrolled. Systemic examination including BaPWV and detailed eye examination were performed. The glaucoma group was divided into subgroups of normal tension glaucoma (NTG, n = 55 ) and primary open-angle glaucoma (POAG) based on an IOP of 21 mmHg. BaPWV was used to stratify the population into 4 groups based on the rate. Stepwise multiple logistic regression analysis by baPWV quartiles was used to compare the glaucoma group with the control group. Main Outcome Measures. BaPWV in glaucoma with DM patients. Results. Faster baPWV was positively associated with glaucoma (odds ratio: 3.74; 95% CI: 1.03–13.56, stepwise multiple logistic regression analysis) in patients with DM. Increasing baPWV was also positively associated with glaucoma (p for trend = 0.036). The NTG subgroup showed similar results to those of the glaucoma group. Conclusions. In this study, increased arterial stiffness was shown to be associated with glaucoma and may contribute to the pathogenesis of glaucoma in DM patients.